2018
DOI: 10.3390/f9030099
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Enzyme Activity of Ectomycorrhizal Fungal Communities Following Nitrogen Fertilization in an Urban-Adjacent Pine Plantation

Abstract: Rapid economic development and accelerated urbanization in China has resulted in widespread atmospheric nitrogen (N) deposition. One consequence of N deposition is the alteration of mycorrhizal symbioses that are critical for plant resource acquisition (nitrogen, N, phosphorus, P, water). In this study, we characterized the diversity, composition, and functioning of ectomycorrhizal (ECM) fungal communities in an urban-adjacent Pinus elliottii plantation under ambient N deposition (~24 kg N ha −1 year −1 ), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 67 publications
1
6
0
Order By: Relevance
“…Similarly, in our study, all N addition treatments (>5 g N m −2 year −1 ) decreased Rs, which suggests that our experimental site reached N-saturation. Some studies reported that the reduction of Rs caused by the decreases of microbial biomass, fine roots, and/or shifts in the microbial community and enzyme functions through excessive N inputs [12,21,29,43]. Actually, the microbial biomass and fine root biomass in the same site decreased after N addition [31], which supported our statement.…”
Section: Soil Respiration In Response To Incremental N Gradientssupporting
confidence: 86%
See 1 more Smart Citation
“…Similarly, in our study, all N addition treatments (>5 g N m −2 year −1 ) decreased Rs, which suggests that our experimental site reached N-saturation. Some studies reported that the reduction of Rs caused by the decreases of microbial biomass, fine roots, and/or shifts in the microbial community and enzyme functions through excessive N inputs [12,21,29,43]. Actually, the microbial biomass and fine root biomass in the same site decreased after N addition [31], which supported our statement.…”
Section: Soil Respiration In Response To Incremental N Gradientssupporting
confidence: 86%
“…However, there is still no consensus on the responses of Rs to litter management in different forest ecosystems [28]. In particular, the effects of incremental N deposition on litter decomposition usually show greater C stabilization through an inhibition of microbial and enzyme activity [29]. Therefore, it is crucial to detangle the effect of litter manipulation on Rs under N additions [30], especially for those of N saturated systems.…”
Section: Introductionmentioning
confidence: 99%
“…The positive effects of N addition on relative abundance of saprotrophic fungi may be supported by the “Gadgil effect,” in which N competition between EcM and saprotrophic fungi could benefit to saprotrophic growth ( Gadgil and Gadgil, 1971 ; Fernandez and Kennedy, 2016 ). Such shifts in fungal community composition could affect the soil enzymatic activities and litter decomposition and, thus, modulate soil C, N, and P cycling in forests exposed to atmospheric N deposition ( Ning et al, 2018 ). Recent studies demonstrated that soil pH and NO 3 – –N concentration were the key drivers influencing fungal community composition ( Francioli et al, 2016 ; Ullah et al, 2019 ; Wang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…These phenomena may reflect the competition for limited organic resources between EcM and saprotrophic fungi, which can be supported by the “Gadgil effect” [ 52 ]. Such shifts in fungal functional composition could affect soil enzymatic activities and litter decomposition, thereby regulating soil biogeochemical cycling in forests exposed to atmospheric N deposition [ 53 ].…”
Section: Discussionmentioning
confidence: 99%